HADIS KEHUJJAHAN HADIS MENURUT IMAM EMPAT MAÅ¼HAB (STUDI ANALISA TERHADAP METODE PENYUSUNAN AL-KUTUB AL-SITTAÄ§ ) - Hidayat, Tatang; Sumarna, Elan (RELIGIA, 2019)
This discussion aims to find out how the four madhab imams explain the hujjah (concept of arguments) of ahad hadith specifically in the al-Kutub al-Sitta? . This discussion used a qualitative approach with a literature study method. Based on the results of the discussion, the four imams have different views on the hujjah of ahad hadith. However, they agreed to use hadith as a secondary source of Islamic laws after the Qur?an. Based on the compilation of all hadith books which belong to al-Ma??dir al-A?l?yah, scholars of the hadith agree that the hadith books of Imam Bukh?r? and Imam Muslim are the most authentic. The implications of this article indicate that the existing hadiths, which are compiled in al-Kutub al-Sitta?, are a collection of hadits that can be scientifically accounted for in terms of their quality, so that it is no doubt to use them as one of the sources of the Islamic laws after the Qur?an.